Reliability and Safety-Driven Availability in Railway Signaling: Quantitative Modeling of Failure Modes, Degraded Operations, and Delay Risk - I Made Arya Pratama I Made Arya Pratama; Ni Luh Putu Sari Dewi Ni Luh Putu Sari Dewi; Bagus Aditya Wicaksana Bagus Aditya Wicaksana (Techne: Journal of Engineering, Technology and Industrial Applications, 2025)
This article presents an applied, quantitative framework that integrates safety-driven system behavior with availability and delay modeling for modern signaling architectures, covering interlocking, track detection (track circuits and axle counters), point machines, wayside signals, and train-to-wayside communication components typical of CBTC/ETCS-like systems. The framework combines reliability block diagrams and Markov availability modeling with delay propagation estimates and decision governance for alarms and degraded-mode escalation, enabling evaluation of design and operational strategies using measurable criteria such as probability of service-impacting unavailability, expected delay minutes per day, false alarm burden, and recovery time distributions. A generic, non-site-specific case design is used to compare three operational strategies: reactive maintenance with conservative degraded working, preventive maintenance with fixed intervals, and condition-based maintenance with governed diagnostics and targeted response. Results show that the largest availability gains typically come from reducing mean time to repair and controlling diagnostic escalation rather than from marginal improvements in component failure rate, and that delay risk is dominated by a small fraction of prolonged incidents where recovery is slowed by troubleshooting ambiguity and operational coordination. The paper also demonstrates that alarm governance and verification pathways materially reduce unnecessary service restrictions without compromising fail-safe principles by ensuring that uncertain faults trigger the least disruptive safe response compatible with evidence quality. Practical outputs include copy-ready tables for reliability and delay KPIs and figure prompts for scientific visualizations suitable for Techne submissions and engineering reporting.